Social-psychological predictors of self-reported actual and intended physical activity in a university workforce sample. Issue 3 (September 1994) - Biddle, S; Goudas, M; Page, A
Abstract : This study investigated the social-psychological predictors of self-reported actual and intended physical activity in a university workforce sample. Based on the 'Theory of Planned Behaviour', but with additional variables of benefits, barriers and self-efficacy, it was found that both intended and actual activity could be predicted but only when strenuous activity was considered. In addition, the predictors were different for men and women. Specifically, the best predictors of intention to exercise were attitude, perceived control, benefits and self-efficacy for women, but only attitude for men. Predicting self-reported strenuous activity for women were intention and self-efficacy, and for men intention and attitude. Theoretical and practical implications for attitude research and exercise promotion are discussed.